2015
DOI: 10.11648/j.jfa.20150301.12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cross-Border Listing on Stock Liquidity: Evidence from East African Community

Abstract: Abstract:The purpose of this study was to examine the impact of cross listing on share liquidity for cross listed firms within East African Community, with the domestic market being the Nairobi Securities Exchange. A census was carried out for Kenyan listed firms that have cross-listed into other EAC exchanges in the last five years. Secondary data was collected from the NSE data base. Stock traded volume and turnover were used as proxy measures of stock liquidity. Their means were calculated pre-and post-cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This suggests that the lower the firms' stock liquidity, the higher their tendency to pursue a dual listing. This is in line with previous studies that showed firms with low liquidity experience an improvement in the stock liquidity after listing abroad (for example, see (Ayyagari & Doidge, 2010;King & Mittoo, 2007;Makau et al, 2015).…”
Section: Regression Analysissupporting
confidence: 92%
See 4 more Smart Citations
“…This suggests that the lower the firms' stock liquidity, the higher their tendency to pursue a dual listing. This is in line with previous studies that showed firms with low liquidity experience an improvement in the stock liquidity after listing abroad (for example, see (Ayyagari & Doidge, 2010;King & Mittoo, 2007;Makau et al, 2015).…”
Section: Regression Analysissupporting
confidence: 92%
“…Currently, countries around the world are forming alliances to overcome the barriers of capital movement, which is found to enhance the competition among investors and market makers, as well as provide wider financial innovations to the investors in their home country (Kariuki, 2015;Kipkemoi, 2013;Makau et al, 2015;Wanjiru, 2013). The integration of capital markets enhances the competition between stock markets and investors in trading in foreign securities (Kariuki, 2015;Yao et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations